Impact of glucocorticoid receptor gene (NR3C1) polymorphisms in Turkish patients with metabolic syndrome - AKKİPRİK, MUSTAFA; ÖZER, SIDIKA AYŞE (SPRINGER, 2016)
Background The metabolic syndrome (MetS) is characterized by a cluster of metabolic factors, including insulin resistance and type-2 diabetes, abdominal obesity, dyslipidemia, hypertension and microalbuminuria. Impaired glucocorticoid receptor (GR) activity also plays an important role in the etiology of MetS. The objective of our study is to evaluate the effects of GR gene polymorphisms (BclI, N363S, TthIII1 and ER22/23EK) in Turkish patients with MetS. Materials and methods Seventy subjects with MetS and 185 healthy controls were enrolled in the study. PCR-RFLP analysis was used for genotyping. Results for each polymorphism have been verified by allele-specific oligonucleotide analysis. Results BclI GG genotype was significantly associated with an increased risk of MetS (p = 0.02). Also, only in women, the G allele carriers were significantly associated with higher C-peptide. T allele carriers of TthIII1 polymorphism were significantly associated with higher C-peptide, triglyceride, insulin and C-reactive protein (CRP, p value 0.048, 0.022, 0.005 and 0.022, respectively), and lower fasting blood glucose (FBG, p = 0.02). The combined carriers of BclI polymorphism G allele and TthIII1 polymorphism T allele were significantly associated with higher diastolic blood pressure in all patients, and lower FBG and postprandial blood glucose in only men. All the ER22/23EK polymorphisms coexisted with polymorphic variant of TthIII1 (p = 0.0058). Conclusion The presence of homozygote polymorphic variant of BclI might be good predictive markers for the disease susceptibility. The BclI and the TthIII1 polymorphism are associated with sex-specific clinical parameters. Our findings also suggest that the combination of BclI and TthIII1 polymorphisms may play a protective role in blood glucose.
Keywords: Metabolic syndrome; Glucocorticoid receptor gene; Glucocorticoid; C-REACTIVE PROTEIN; FRAGMENT-LENGTH-POLYMORPHISM; PITUITARY-ADRENAL AXIS; IN-VIVO; CHINESE POPULATION; ASSOCIATION; SENSITIVITY; STRESS; RISK; BCLI